Talkīn Dead Before and After Buried; an Analysis of the al-Shafi'i and Maliki Schools of Thought - Tabran, Muhammad; Talli, Abdul Halim (Universitas Islam Negeri Alauddin Makassar, 2021)
This article examines the analysis of the views of the al-Shafi'i and Maliki schools on the talqīn of the dead before and after being buried. The type of research used by the author in this study is a qualitative research type, which is a type of research that brings library research data sources in the form of books or other scientific works. using a normative approach (shari'a), which is an approach to the problem that will be studied based on texts in the Qur’an, Sunnah, and Ijmak of the scholars and obtained from various literatures related to the problems that the author will discuss, both sourced from primary and secondary data. secondary data. The results of this study found differences in views between the scholars of the al-Shafi'i School and the Maliki School regarding the legal status of talqīn before and after burial, using the legal istinbath technique of each school. The al-Shafi'i school of thought is of the view that the law of talqin before being buried or in a state of death is sunnah as well as after being buried based on the arguments and istinbath of the school's law. Unlike the Maliki school of thought, the law of talqīn before burial is sunnah, and the law of talqīn after being buried is makruh, based on the legal argument that after burial it is considered weak. Keywords: Talqīn Dead; Burial; al-Sha’fii School; Maliki School.